(untitled) (Journal of the College of Basic Education, 2022)
This study aimed to reveal the effectiveness of group counseling program based on behavioral cognitive theory in improving the communication skills of mothers and its impact on the reduction of aggressive behavior, and improving the Learning for their pre-school children in Jordan. To achieve that the counseling program has been established with three measurements: the first one measure Communication skills among mothers, the second one: measures aggressive behavior, and the third one, identify improve learning in children. The study sample consist of (30) mothers of children in Um Ammar school Girls High school of directorate of education brigade Marka, which selected randomly out of 500 mothers and divided into two groups. The experimental group consists (15) mothers and the control group consists of (15) mothers. Data were analyzed using descriptive statistics and ANCOVA. The study findings show There are statistically significant differences between the both groups: the experimental group which exposed to collective program and the control group which does not exposed the collective counseling program, in improving the communication skills of mothers, and reducing the aggressive behavior, and improving the Learning for their pre-school children. No significant differences were found between experimental and controlled group aggressive behavioral total mean scores according to the educational level variable.